The 2021 Nobelists: Lessons for Higher Education, Science, and Society - Altbach, Philip; DeLaquil, Tessa (International Higher Education, 2022)
The 2021 Nobel prizes in science reveal much about trends in higher education and science. They show that only top global universities produce Nobelists and that the winners are educated at top universities. The United States and United Kingdom currently have an advantage. Nobel laureates are born in a diversity of countries but often migrate to the United States. The 2021 Nobelists in the sciences include no women—and women are in general dramatically underrepresented.